EPB41, a novel hepatoma susceptibility gene dysregulated by c-Myc: an integrative functional genomics study. (October 2016) - Yang, Xinyu; Yu, Dianke; Ren, Yanli; Wei, Jinyu; Pan, Wenting; Zhou, Changchun; Zhou, Liqing; Liu, Yu; Yang, Ming
Abstract: Background: Genome-wide association studies (GWAS) have provided insight into cancer genetics. However, molecular mechanisms whereby many susceptibility single nucleotide polymorphisms (SNPs) identified by GWAS promote cancer heritability and risk are unknown. New research strategies to evaluate functionality are needed to systematically study causal genetic variants. Methods: In this study, we developed an integrative functional genomics method to identify cancer susceptibility SNPs in transcription factor binding sites across the whole genome. By integration of functional genomic data from c-Myc cistromics, 1000 Genomes and the TRANSFAC matrix databases, we identified SNPs in the c-Myc cistrome that might modulate c-Myc binding affinity in hepatocellular carcinoma. We took blood samples from patients with hepatitis B-related hepatocellular carcinoma who were admitted to Shandong Cancer Hospital, Jinan, Shandong Province. China, or Huaian No. 2 Hospital, Huaian, Jiangsu Province, China. We extracted genomic DNA from these samples and did genotype analyses. Written informed consent was obtained from all participants and the study was ethically approved by the institutional review boards. Findings: We identified 12 SNPs in 1806 people with hepatitis B-related hepatocellular carcinoma, we genotyped these SNPs and 1708 controls. We identified a novel hepatocellular carcinoma susceptibility SNP, EPB41 rs157224 G>T (OR of T allele 1·64 [95% CI 1·32–2·02]; p<0·00001), in Chinese patients with hepatocellular carcinoma. This SNP in EPB41 predisposes individuals to hepatocellular carcinoma through modification of c-Myc-mediated transcriptional regulation; the risk allele has decreased gene expression. EPB41 is a novel hepatocellular carcinoma susceptibility gene. Consistent with this notion, a EPB41 expression is decreased tissue samples from patients with hepatocellular carcinoma, especially portal vein metastasis or intrahepatic metastasis. Interpretation: Our results show that SNP EPB41 rs157224 G>T could be associated with increased susceptibility to hepatocellular carcinoma and show that insight into malignancy pathology can be made using a genome-wide approach. Funding: National Natural Science Foundation of China (81201586 and 31271382), National High-Tech Research and Development Program of China (2015AA020950), State Key Laboratory of Molecular Oncology (SKL-KF-2015-05).